Performance analysis of four routing protocols in sensor networks. (21st May 2008) - Bellaachia, Abdelghani; Weerasinghe, Nilkamal
The efficiency of sensor networks strongly depends on the routing protocol used. In this paper, we analyse four different types of routing protocols: LEACH, PEGASIS, HIT-M, and DIRECT. Sensor networks were simulated using TOSSIM simulator. Several experiments were conducted to analyse the performance of these protocols including the power consumption and overall network performance. The experimental results show that HIT-M outperforms all other protocols while PEGASIS has better performance than LEACH and DIRECT. LEACH and DIRECT have similar performance. This paper also shows the power consumption for all protocols. On the average, DIRECT has the worst power consumption.